Komunikasi Data Menggunkan Topologi Tree - Nazwa Amelia Purnama; Muhammad Dicky Saputra; Gilang Nur Rosyid; Paul Manurung; Didik Aribowo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
In the era of digital communication, access speed and data security are crucial. The study evaluated network topology, focusing on tree topology using simulations with Cisco Packet Tracer. Tests highlighted stability, latency, throughput, and bottleneck potential. Data transmission time information is key in assessing network performance. Test results are important for optimizing performance and identifying areas of improvement in the network. In conclusion, monitoring network performance is an important step for operational efficiency and security.